End of Course Feedback: A Reflective Look at What Is Really Helpful and A Proposal For Change - Denise Krupp (Journal of Scholarly Engagement)
College student end-of-the-semester evaluations of their college instructors and class experiences are meant to be used as a tool to reflect on the success of teaching effectiveness and future changes needed. However, these evaluations are limited, come after the semester has ended, and have many confluent factors affecting the outcome. Ideally, useful assessments need to be given regularly, providing a clearer picture of the class needs and assessing not only the classroom experience but also the relationship with the instructor. This reflection is one instructor’s insight into the need for ongoing student feedback in the classroom. It will show the importance of not only teaching effectively by getting regular feedback from students but also the importance of developing rapport and alliance in the classroom, which is a factor in increasing student learning satisfaction. Over the years, the counseling profession has adapted a way for clients to provide regular feedback on the client/counselor relationship. The feedback provides regular and consistent information for the therapist on how the therapeutic process and relationship are doing. This feedback is a relatively new trend in counseling, and now many agencies are implementing a form of it. This style of getting feedback from the client is a type of “customer satisfaction” survey. It provides counselors with real-time feedback on clients’ perceptions and can provide a springboard for dialogue for change. While there are many differences between counseling and teaching, this style of regular feedback may enhance classroom instruction.